Unemployment in women with psychosocial disabilities during the COVID‐19 pandemic: Lessons from Tana River County, Kenya. (25th February 2022) - Ebuenyi, Ikenna D.; Gitonga, Isaiah; Tele, Albert; Syurina, Elena V.
Abstract: In low‐income settings, the informal economy is a practical alternative to work and employment for persons with disabilities. However, the COVID‐19 pandemic negatively affected the informal economy. This study aimed to explore the experiences of women with psychosocial disabilities in Kenya during the pandemic. We found that the pandemic worsened their experiences of work and employment, and they did not receive any social welfare or support from the government. Our findings suggest that pandemic management must adopt inclusive and context‐sensitive approaches that support persons with psychosocial disabilities. Social welfare and protection for persons with disabilities are relevant for socio‐economic empowerment and inclusion.